Cost Effective Deposition of Aluminium Oxide Layers - I.A. Khan; A. Rashid; A. Fatima; M.A.K. Shahid; T.H. Bokhari; R. Ahmad (Journal of Basic & Applied Sciences, 2013)
Al2O3 surface-layers were deposited on Al substrates by thermal evaporation technique. Samples were treated for different (1 h, 2 h, 3 h, 4 h and 5 h) treatment time in open air environment by keeping the temperature (550oC) of the evaporator plate constant. XRD patterns revealed the emergence of Al2O3 H2O (111), Al (OH)3 (214) and Al2O3 (20 6) planes. Crystallinity of the above mentioned phases was attributed with treatment time. However, minimum treatment time to break oxygen hydrogen bonds and the formation of Al2O3 plane was 5 h. Crystallite size and compressive stress found in Al2O3 (2 0 6) plane were 14.31 nm 0.53 GPa respectively. SEM microstructure features revealed the formation of rounded grains, irregular patches and rods. AFM analysis exhibited the formation of dome shapes microstructures. The grain size and surface roughness were increased from 1 ?m to 2.5 ?m and from 35 nm to 115 nm respectively. This variation in surface roughness and grain sizes was associated with treatment time.